PENGARUH SURPLUS ARUS KAS BEBAS, UKURAN PERUSAHAAN, LEVERAGE, DAN KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Irma Wahyu Lupita; Wahyu Meiranto (Diponegoro Journal of Accounting, 2018)
This study aims to examine the effect of surplus free cash flow, firm size, leverage, and audit quality on earnings management of manufacturing companies. The dependent variable in this study is earnings management, while the independent variables in this study are surplus free cash flow, firm size, leverage, and audit quality. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sample in this research are 58 manufacturing companies during period 2015-1016. Sample was obtained by using purposive sampling method based on certain criteria. This study uses multiple linear regression analysis method for hypothesis testing. The result show that surplus free cash flow had positive significant effect on earnings management, while audit quality had negative significant effect on earnings management. However, firm size and leverage had not a significant effect on earning management.